2023
DOI: 10.5114/jhk/162017
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning Strategies for Improving Handball Throwing Velocity: A Systematic Review and Meta-Analyses

Abstract: Ball throwing velocity is essential for scoring goals in handball; the crucial question is how to develop throwing velocity in highly trained handball players. Therefore, this systematic review aims to summarize effective conditioning strategies to improve throwing velocity in elite male players and to perform a meta-analysis on which training system can provide the highest increase in throwing velocity. The literature was analyzed using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…The result was based on male elite [ 14 , 28 , 59 61 ] and amateur handball players [ 12 ] and females competitive players [ 10 ]. These findings are in agreement with previous results of a systematic review [ 34 ], which showed that weight training with moderate and high intensity (> 55% of 1RM) was the best strategy to improve throwing velocity. The previous analysis included only elite players while the results of this systematic review generalize the effects of weight training beyond elite male handball players.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The result was based on male elite [ 14 , 28 , 59 61 ] and amateur handball players [ 12 ] and females competitive players [ 10 ]. These findings are in agreement with previous results of a systematic review [ 34 ], which showed that weight training with moderate and high intensity (> 55% of 1RM) was the best strategy to improve throwing velocity. The previous analysis included only elite players while the results of this systematic review generalize the effects of weight training beyond elite male handball players.…”
Section: Discussionsupporting
confidence: 93%
“…Another systematic review from Garcia et al [ 33 ] included studies with various overhead athletes (baseball, volleyball, tennis, softball, cricket, water polo, and handball) and they concluded that specific RT for the enhancement of throwing velocity has a significant effect in all populations (male teenagers, male adults, female adults). In addition, a recent systematic review [ 34 ], concluded that RT is the most effective strategy for improving throwing velocity in elite handball players. Ηowever, this study did not investigated the influence of RT on throwing velocity in male and female non-elite handball players as well as elite females.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the player's maximum throwing speed plays a greater role since the maximum interrelationship between speed and accuracy does not coincide with the player's maximum speed (Fitts, 1954). In short, throwing speed is a critical factor in competition but the question is how throwing speed and accuracy differ in stable and competition conditions (Petruzela et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The physical and physiological characteristics and the on-court performances of handball players have recently been reviewed (4,5). It is a contact sport, which includes jumping, running, changes of direction and arm throwing ball as prominent features of performance (6)(7)(8)(9). Muscle strength and power are key components of fitness performance, required in many explosive actions (e.g., jump, change of direction, throw, sprint) and constitute an essential part of any young athlete's overall training program (10).…”
Section: Introductionmentioning
confidence: 99%